Good Morning Young People: Geronimo Fm Radio's Efforts To Maintain Existence In Generation Z - Nu”azzidane, Bakhtiar Rafqi; Sa’idah, Zahrotus (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
Geronimo FM is a radio that was established in 1971. It was the first national private radio in Yogyakarta that not only became a music barometer, but also provided various information about the world of entertainment, arts and culture and the lifestyle of young people. Nowadays, almost all people including generation z rarely listen to radio. Thus, the researcher examines the efforts of Geronimo FM radio in maintaining its existence in generation z. Therefore, the purpose of this research is so that generation z can regain interest in radio. The research method used is qualitative method. For data collection techniques, this research explains the results based on participant observation, semi-structured interviews with the main source Leila Karina, supporting sources Pamungkas Kusuma Sakti, and finally documentation. Furthermore, for data analysis using data reduction by selecting data, data display, and conclusions. The results of the study explain that Geronimo FM's efforts to maintain their existence in the decline in the number of listeners, especially in generation z through the Good Morning Youngste program, namely generating (Attention) by creating content, growing (Interest) by curating the selection of info, generating (Desire) by creating an activity, doing (Decision) by collaborating with digital media and doing (Action) by finding out what trends are being discussed by generation z, so that generation z has a sense of interest in radio again.